Approvisionnement Et Commercialisation De Deux Espèces De Francolin Utilisées Comme Oiseaux Gibiers Au Bénin - Richard, Avado C.; Toussaint, Lougbegnon O.; François, Gbesso G. H.; Claude, Codjia Jean T. (European Scientific Journal, ESJ, 2018)
The two species of francolin used as game birds in Benin are Francolinus albogularis Hartlaub and Francolinus bicalcaratus Linnaeus belong to the family Phasianidae. This study aims to evaluate the importance of the commercialization of these game birds at the level of the different actors involved in the value chain. Data collection is based on structured and semistructured surveys conducted at the outlets of species along inter-state roads, in restaurants and hotels, public dining places and bushmeat markets as well than consumers. In total, 495 people were surveyed. The data collected is essentially the actors of the marketing chain, the evolution of the price variation of an individual of francolin, the different transaction circuits, the places of supply. The Minitab 16 software, with the descriptive statistical function, was used to assess the evolution of the price of a francolin individual over the last thirty years among the actors of the marketing circuit. Calculated meat supply frequencies and Kruskal-Wallis tests were performed. The results from the analysis of the data show that three main actors intervene in the distribution of the product, a varaiation of frequency of supply of the meat, the price of sale of an individual of francolin rose from 50 FCFA there is thirty years to 1600 FCFA this day at the level of hunters. For women processors, this price went from 200 FCFA twenty years ago to 1500 FCFA that day; while he spent for the same period from 300 FCFA to 3500 FCFA among the tenants of restaurants and hotels. This shows a consequent increase in prices. The Kruskal-Wallis test revealed a significant difference between the average selling prices of an individual francolin by hunters from thirty years ago, twenty years, ten years, five years ago and then today. It follows from all the above that urgent measures are being taken to adopt a domestication model for the multiplication of individuals and the valorization of francolins’ meat.